Laser cutting of polymeric materials: An experimental investigation - Choudhury, Imtiaz Ahmed; Shirley, S. (Elsevier, 2010)
The CO(2) laser cutting of three polymeric materials namely polypropylene (PP), polycarbonate (PC) and polymethyl methacrylate (PMMA) is investigated with the aim of evaluating the effect of the main input laser cutting parameters (laser power, cutting speed and compressed air pressure) on laser cutting quality of the different polymers and developing model equations relating input process parameters with the output. The output quality characteristics examined were heat affected zone (HAZ), surface roughness and dimensional accuracy. Twelve sets of tests were carried out for each of the polymer based on the central composite design. Predictive models have been developed by response surface methodology (RSM). First-order response models for HAZ and surface roughness were presented and their adequacy was tested by analysis of variance (ANOVA). It was found that the response is well modeled by a linear function of the input parameters. Response surface contours of HAZ and surface roughness were generated. Mathematical model equations have been presented that estimate HAZ and surface roughness for various input laser cutting parameters. Dimensional accuracies of laser cutting on polymers were examined by dimensional deviation of the actual value from the nominal value. From the analysis, it has been observed that PMMA has less HAZ, followed by PC and PP. For surface roughness, PMMA has better cut edge surface quality than PP and PC. The response models developed can be used for practical purposes by the manufacturing industry. However, all three polymeric materials showed similar diameter errors tendency in spite of different material properties. (C) 2009 Elsevier Ltd. All rights reserved.